Costello syndrome: two cases with embryonal rhabdomyosarcoma. Issue 12 (December 1998) - Kerr, B; Eden, O B; Dandamudi, R; Shannon, N; Quarrell, O; Emmerson, A; Ladusans, E; Gerrard, M; Donnai, D
Abstract : Costello syndrome is a well delineated mental retardation syndrome of unknown aetiology in which the occurrence of benign tumours, especially papillomata, is recognised. We report two children in whom the diagnosis of Costello syndrome was made in the first months of life, who both developed a retroperitoneal embryonal rhabdomyosarcoma. Although not previously reported, the occurrence of this relatively uncommon childhood tumour in two girls with Costello syndrome suggests that an increased risk of malignancy may be part of this condition. The genetic basis of this susceptibility requires further clarification.